Investigation of QCM Sensor coated with Biosynthesized Nanomaterial to detect major volatile in Indian Cumin - Malik, Subhojit; Ghosh, Amar; Basak, Amrik; Sur, Ujjal Kumar; Sharma, Prolay (Devices for Integrated Circuit, 2025)
A highly sensitive and selective Quartz Crystal Microbalance (QCM) gas sensor has been developed to detect volatile present in Indian cumin. Fresh rose petals, R. damascena, have been utilized to generate a natural bio-coating material. The pink-colored extract was prepared after cleaning and boiling the petal pieces in Milli-Q water followed by filtration. This extract was used to synthesize gold nanoparticles by mixing it with HAuCl4 solution, resulting in a color change from light yellow to deep pink, indicating nanoparticle formation. The nanoparticles were separated through centrifugation and deposited onto the QCM surface. The sensor fabrication process involved 15 coating cycles, achieving maximum mass deposition, with the initial frequency of 9994862 Hz decreasing by 4352 Hz. Chronogram analysis revealed the mass and frequency variation during the process. The sensors were tested with the volatile compounds in Indian cumin, identified by GC-MS analysis and the sensor is responsive in detecting α-Pinene present in Indian cumin. The biosynthesized sensor had a sensitivity value of 0.1987 Hz/mgL⁻¹ with a high correlation factor (R2 = 0.9917). The results show that the sensor was successfully fabricated by using naturally derived nanomaterials, which presented high sensitivity and reusability. This study therefore points out that biosynthesized nanomaterials can be used as eco-friendly and effective coating materials in sensor development.